2020
DOI: 10.1177/0020764020922276
|View full text |Cite
|
Sign up to set email alerts
|

Very long-term outcome of psychotic disorders

Abstract: Background: The outcome of schizophrenia and related psychoses is generally modest, and patients display high rates of disability. Aims: The aim of the review is to present an up-to-date account of the research on the very long-term outcome of psychotic disorders. Method: We conducted a search in the PubMed and Scopus databases for articles published since the publication of the very long-term data of the World Health Organization’s International Study of Schizophrenia (the ISoS study), over the last 18 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…The following registers hold complete and updated data in real time on all participants (not deceased or emigrated) on a range of relevant outcomes: (1) addresses and vital status was drawn from the Danish Civil Registration System, 34 (2) information about psychiatric service use (days of psychiatric hospitalizations, number of psychiatric outpatient contacts) was extracted from the Danish Psychiatric Central Register, 35 (3) use of supported housing and homeless shelters at the previous year up to 20-year follow-up was obtained by linking information from the official Danish national website Tilbudsportalen with addresses of all supported housing facilities and homeless shelters in Denmark with individual-level address information in the Danish Civil Registration System register 34 as described in a previous publication, 36 (4) mortality and cause of death was drawn from the Cause of Death Registry, 37 and (5) vocational status was available from the DREAM database. 38 Registry data were collected for all individuals regardless of participation in the assessments and is thus free from attrition.…”
Section: The Danish Registry Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The following registers hold complete and updated data in real time on all participants (not deceased or emigrated) on a range of relevant outcomes: (1) addresses and vital status was drawn from the Danish Civil Registration System, 34 (2) information about psychiatric service use (days of psychiatric hospitalizations, number of psychiatric outpatient contacts) was extracted from the Danish Psychiatric Central Register, 35 (3) use of supported housing and homeless shelters at the previous year up to 20-year follow-up was obtained by linking information from the official Danish national website Tilbudsportalen with addresses of all supported housing facilities and homeless shelters in Denmark with individual-level address information in the Danish Civil Registration System register 34 as described in a previous publication, 36 (4) mortality and cause of death was drawn from the Cause of Death Registry, 37 and (5) vocational status was available from the DREAM database. 38 Registry data were collected for all individuals regardless of participation in the assessments and is thus free from attrition.…”
Section: The Danish Registry Datamentioning
confidence: 99%
“…2 The lifetime risk for receiving a diagnosis of schizophrenia has been estimated to be 1.8%. 3 A recent review including 16 studies with at least 15 years of follow-up found individuals with schizophrenia to have a poorer long-term prognosis than individuals diagnosed with other schizophrenia spectrum disorders 4 with inconsistencies of good outcomes ranging from 8% to 74%. 4 Also, metaanalyses on recovery after a schizophrenia diagnosis have been inconsistent with rates ranging from 14% to 57%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among psychiatric disorders schizophrenia and related syndromes are still the most devastating, according to the recent Global Burden of Disease Study [ 4 ]. Schizophrenia is a severe and chronic mental illness, with generally modest prognosis and often poor long-term outcome [ 5 , 6 ]. The syndrome comprises a wide range of symptoms, such as positive and negative symptoms and cognitive impairment, that adversely affect social and occupational functioning of patients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenia and related syndromes (the so-called psychotic disorders) are severe and chronic mental disorders that are characterized by a wide range of disabling symptoms. The prognosis of these disorders is generally modest, outcomes are often poor, and patients may display high rates of disability (Jääskeläinen et al, 2013; Peritogiannis, Gogou, et al, 2020). Research on these severe disorders is growing over the last decades, and has addressed several issues regarding incidence and prevalence, underlying pathophysiological mechanisms, and treatment (Marder & Cannon, 2019; Owen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%